Selective Targeting of Proteins by Hybrid Polyoxometalates: Interaction Between a Bis-Biotinylated Hybrid Conjugate and Avidin - Zamolo, Valeria A.; Modugno, Gloria; Lubian, Elisa; Cazzolaro, Alessandro; Mancin, Fabrizio; Giotta, Livia; Mastrogiacomo, Disma; Valli, Ludovico; Saccani, Alessandra; Krol, Silke; Bonchio, Marcella; Carraro, Mauro (Frontiers in Chemistry, 2018)
The Keggin-type polyoxometalate [γ-SiW10O36]4- was covalently modified to obtain a bis-biotinylated conjugate able to bind avidin. Spectroscopic studies such as UV-vis, fluorimetry, circular dichroism, coupled to surface plasmon resonance technique were used to highlight the unique interplay of supramolecular interactions between the homotetrameric protein and the bis-functionalized polyanion. In particular, the dual recognition mechanism of the avidin encompasses (i) a complementary electrostatic association between the anionic surface of the polyoxotungstate and each positively charged avidin subunit and (ii) specific host-guest interactions between each biotinylated arm and a corresponding pocket on the tetramer subunits. The assembly exhibits peroxidase-like reactivity and it was used in aqueous solution for L-methionine methyl ester oxidation by H2O2. The recognition phenomenon was then exploited for the preparation of layer-by-layer films, whose structural evolution was monitored in situ by ATR-FTIR spectroscopy. Finally, cell tracking studies were performed by exploiting the specific interactions with a labeled streptavidin.